Konstitusionalisme Lingkungan dalam Kebijakan Pembangunan Ibu Kota Nusantara - Muhammad Suhardi (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2025)
This study aims to analyze the development of Indonesia’s Nusantara Capital City from the perspective of environmental constitutionalism by positioning the right to a good and healthy environment as the main standard of assessment. The study responds to the problem that IKN is framed as a green city, forest city, and low-carbon development project, while it may still generate ecological risks, spatial transformation, pressure on natural resources, and injustice for local communities and future generations. This research employs a qualitative method with a normative juridical approach. The analysis uses statutory, conceptual, and policy case-study approaches to examine the development of IKN. The data sources consist of primary legal materials, secondary legal materials, policy documents, and relevant academic literature. The findings show that the formal legality of IKN development is not sufficient to ensure its conformity with environmental constitutional principles. IKN development must be assessed through ecological legality, the precautionary principle, meaningful public participation, protection of local communities, intergenerational justice, and ecological accountability. The contribution of this study lies in proposing green constitutionalism as an evaluative framework for IKN development, so that the vision of a green capital city does not remain a policy narrative but becomes a constitutional obligation that can be legally and publicly tested.